Prevalence of perceived stress among clinical students of Bayero University Medical School - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The academic and psychological demands of undergraduate medical education may result in high-stress levels among students. High stress has been associated with poor academic performance, negative impact on physical and mental health. This study aims to determine the prevalence of stress among undergraduate clinical students of Bayero University Kano Medical School.Materials and Methods:This was a cross sectional study conducted among 224 clinical medical students from levels 400–600. The Cohen’s Perceived stress scale (PSS-10) was used to assess the severity of among the students. The Chi-square test was used to determine associations and a significant association was considered atP< 0.05.Results:A prevalence of high stress of 59.8% was observed with a mean PSS score of 20.76 ± 5.58. The highest mean score of 22.29 ± 5.58 was observed among 400 level clinical students. There was no significant difference between both genders. A significantly higher proportion of students undergoing medicine, pathology, paediatrics and surgery postings were observed to be experiencing a higher level of perceived stress compared to those in Obstetrics and Gynaecology, (χ2= 1617, df = 4,P< 0.05). Similarly, a higher proportion of students whose fathers are educated had a significantly higher stress compared to their counterparts from uneducated backgrounds, (χ2= 5.54, df = 1,P< 0.05).Conclusion:Further studies to determine the causes of stress need to be carried out. This will assist the students and teachers to appropriately manage stress.